Institutions judiciaires et adolescents au Burkina Faso: des modèles de punitions endogènes et contemporaines - Sanou, Doti Bruno (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
“This study on ‘patterns of punishment in the Bobo community of Bobo-Dioulasso’ presents in the first part the geographical situation of Bobo communities, their population and their social organization. The second part of the report presents the results of interviews conducted with various resource persons, 10 of whom were involved in carrying out this study in the Bobo community in the Bobo-Dioulasso area. These included teacher-researchers, historians, the Catholic University of West Africa, administrative, customary and religious authorities.”
Keywords: Administration of Justice; Teenagers; Youth; Punishment